Capturing the moment: facilitating learning from the margins. A photographic essay - Kevin J. Brazant (Journal of Learning Development in Higher Education)
The author provides a case study of third space innovation, a professional's reflection on practice, focusing on a learning developer's approach to facilitating group learning from the margins. The author defines this as facilitated learning that prioritises the experiences, voices and needs of individuals or groups who are typically underrepresented, underserved or marginalised. It is an approach that shifts focus away from mainstream or dominant perspectives to ensure that diverse viewpoints and experiences are acknowledged and included in the learning process. It signals a new direction for research into the 'facilitation process' in learning development. The author uses photographic essay methodology to explore this as part of a meta-reflective account (Rianne and Huib, 2019). The approach enables the author to punctuate critical moments of group facilitation with visual illustrations to aid analysis and reflection. The themes of interdisciplinary approaches to group work and collaborative experiences in learning development are explored. Collaboration can create opportunities for third space individuals to gain professional and personal empowerment and agency (Abegglen, Burns and Sinfield, 2023).